Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite